[SbW9O33]-based polyoxometalate combined with a phase transfer catalyst: A highly effective catalyst system for selective oxidation of alcohols with H2O2, and spectroscopic investigation - Ingle, Rohit H.; Raj, N. K. Kala; Manikandan, Palanichamy (Journal of Molecular Catalysis A-Chemical, 2007)
Na-9[SbW9O33] in conjunction with a phase transfer catalyst, methyltricapryl ammonium chloride, is highly efficient for selective oxidation of variety of alcohols with aq. H2O2 to yield corresponding carbonyls. Most importantly the reactions are carried out in the absence of any organic solvents especially halogenated solvents. In case of allylic alcohols, the catalyst is highly selective for the alcohol oxidation reaction and least selective for epoxidation reaction in the presence of aq. H2O2. IR studies support the formation of W-peroxo intermediate species and also support the stability of the catalyst in the presence of phase transfer compound under the present experimental condition. The catalyst can be reused after careful decomposition of peroxide of the final reaction mixture. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Alcohol; Aq.H2O2; Nag[SbW9O33]; Oxidation; Phase transfer catalyst; Polyoxometalate; polyoxotungstate